Spatial Distribution and Abundance of Small Cetaceans in the Pacific Waters of Guatemala - Quintana-Rizzo, Ester; Cabrera, Andrea A.; Ortiz-Wolford, Jenniffer; Dávila, Vanessa (Frontiers in Marine Science, 2021)
The establishment of marine protected areas (MPAs) requires a thorough assessment of the abundance, distribution, and habitat preferences of a variety of marine species. Small cetacean spatial distribution and abundance were examined in the Pacific waters of Guatemala to provide this information. Boat surveys were conducted for 38 months between January 2008 and June 2012. A total of 64,678 cetaceans in 505 sightings from nine Delphinidae species were recorded. Three species, referred to as common species, accounted for 90% (n = 456) of all sightings. They included Tursiops truncatus (56%, n = 278), Stenella attenuata (29%, n = 143), and Stenella longirostris (7%, n = 35). Group size was significantly different among the common species (p < 0.001). S. longirostris had the largest group size (444 ± 75 dolphins), followed by S. attenuata (28 ± 5 dolphins), and T. truncatus (15 ± 2 dolphins). T. truncatus was the most common in the study area (0.02 ± 0.002 sightings/km of survey effort), and S. attenuata (0.37 ± 0.16 dolphins/km) and S. longirostris (1.62 ± 0.41 dolphins/km) were the most abundant in the neritic (≤200 m depth) and oceanic zones (≥200 m depth), respectively. The wide-ranging distribution of T. truncatus overlapped with the distribution of S. attenuata in the neritic zone and S. longirostris in the oceanic zone. Little overlap was observed in the distribution of S. attenuata and S. longirostris. Most hot spots (∼66%) were in the oceanic zone and no hot spots were near or in the MPAs. Hot spots were identified along the 200 m isobath, the Middle America trench, and the San José Canyon. These could be areas of high productivity where dolphins concentrate to feed. To the north of the San José Canyon, five species of small cetaceans were observed in a stretch of the neritic zone including three MPAs. No other section of this zone had such high diversity. Results need to be taken with caution given the small sample size. Our results suggest that the protection of small cetaceans needs to consider the creation of oceanic MPAs that should be integrated into the existing network.